USING SEDIMENT ORGANIC GEOCHEMISTRY TO INTERPRET LATE HOLOCENE BARRIER ISLAND AND ESTUARINE EVOLUTION, NORTH CAROLINA, USA - Minnehan, Jeffrey J. (East Carolina University, 2014)
Deconvolving the relationship between meteorological and oceanographic phenomena and associated impacts to coastal systems is critical to understanding the future of coastal systems worldwide. North Carolina's barrier islands, commonly known as the Outer Banks, and the associated Albemarle-Pamlico estuarine system is an example of a coastal ecosystem that will be affected in the future by such phenomena. Based on sedimentological and micropaleontological proxies, past research suggests that intense storm activity may have caused extensive segmentation of the Outer Banks during the Holocene. To gain a better understanding of meteorological and oceanographic factors affecting the evolution of North Carolina's coastal system, organic geochemical techniques were applied to sediments from two cores collected within Pamlico Sound. Specifically, down-core trends in total organic carbon (TOC), refractory black carbon (BC), refractory soot carbon, labile organic carbon (OC), total nitrogen (TN), and their stable isotopic signatures ([delta]¹³C and [delta]¹⁵N) were analyzed in order to assess the varying inputs of marine and terrestrial organic matter into Pamlico Sound. In Chapter 1, TOC, BC/TOC, soot/TOC, TOC/TN, and [delta]¹³C[subscript]TOC were compared to a paleoclimatological proxy of El Niño Southern Oscillation (ENSO) and interpretations of stages of the North Atlantic Oscillation (NAO) throughout the mid-to-late Holocene. These phenomena have been suggested to influence southeast U.S. temperature, precipitation, and Atlantic hurricanes, all of which ultimately affect barrier island and estuarine evolution, as recorded in Pamlico Sound sediments. In general, there has been little consideration of carbon sequestered in coastal systems throughout the Holocene, a period that shows anthropogenic changes in the carbon cycle. This is an important omission, as most of the sediments exported by the world's major rivers are currently deposited on continental shelves (e.g., deltas and estuaries). Chapter 2 examines how the degree of barrier island segmentation affects abundance and source of carbon sequestered in Pamlico Sound throughout the mid-to-late Holocene. Total organic carbon sequestered in Pamlico Sound was calculated over the past 3500 years. Since the ultimate fate of TOC depends on its composition (e.g., whether it is labile or refractory), both OC and BC in sediments were quantified down-core. Results show that greater continuity of a barrier island chain significantly increased the amount of carbon sequestered in sediments. To our knowledge, this chapter provides the first quantitative estimate of the amount of carbon sequestered as a function of its composition since the mid-Holocene in any coastal system. The results of both chapters suggest that ENSO, NAO, eastern North Carolina temperature and precipitation, Atlantic storm activity, Outer Banks barrier island evolution, and coastal carbon sequestration were linked throughout the mid-to-late Holocene.
Keywords: Geochemistry; Geology; Black carbon; Carbon sequestration; Holocene; Paleoclimate; Stable isotopes; Environmental geomorphology--North Carolina; Barrier islands--North Carolina; Coastal sediments--North Carolina; Sedimentation and deposition--North Carolina; Paleoclimatology--North Carolina--Holocene; Sounds (Geomorphology)--North Carolina; Pamlico River (N.C.); Pamlico Sound (N.C.); Albemarle Sound (N.C.)